Seasonal vertical surface thaw displacement in 2018 on Samoylov Island (Lena Delta, northeastern Siberia) measured by satellite SAR interferometry with X-, C- and L-band sensors - Tazio Strozzi; Nina Jones; Julia Boike; Sofia Antonova; Birgit Heim; Silvan Leinss; Urs Wegmüller; Sebastian Westermann; Andreas Kääb; Guido Grosse; Annett Bartsch (Remote Sensing of Environment, 2026)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

Permafrost-thaw lake development in Central Yakutia: sedimentary ancient DNA and element analyses from a Holocene sediment record - Izabella Baisheva; Luidmila Pestryakova; Sardana Levina; Ramesh Glückler; Boris K. Biskaborn; Stuart A. Vyse; Birgit Heim; Ulrike Herzschuh; Kathleen R. Stoof-Leichsenring (Journal of Paleolimnology, 2023)
In Central Yakutia (Siberia) livelihoods of local communities depend on alaas (thermokarst depression) landscapes and the lakes within. Development and dynamics of these alaas lakes are closely connected to climate change, permafrost thawing, catchment conditions, and land use. To reconstruct lake development throughout the Holocene we analyze sedimentary ancient DNA (sedaDNA) and biogeochemistry from a sediment core from Lake Satagay, spanning the last c. 10,800 calibrated years before present (cal yrs BP). SedaDNA of diatoms and macrophytes and microfossil diatom analysis reveal lake formation earlier than 10,700 cal yrs BP. The sedaDNA approach detected 42 amplicon sequence variants (ASVs) of diatom taxa, one ASV of Eustigmatophyceae ( Nannochloropsis ), and 12 ASVs of macrophytes. We relate diatom and macrophyte community changes to climate-driven shifts in water level and mineral and organic input, which result in variable water conductivity, in-lake productivity, and sediment deposition. We detect a higher lake level and water conductivity in the Early Holocene (c. 10,700–7000 cal yrs BP) compared to other periods, supported by the dominance of Stephanodiscus sp. and Stuckenia pectinata . Further climate warming towards the Mid-Holocene (7000–4700 cal yrs BP) led to a shallowing of Lake Satagay, an increase of the submerged macrophyte Ceratophyllum, and a decline of planktonic diatoms. In the Late Holocene (c. 4700 cal yrs BP–present) stable shallow water conditions are confirmed by small fragilarioid and staurosiroid diatoms dominating the lake. Lake Satagay has not yet reached the final stage of alaas development, but satellite imagery shows an intensification of anthropogenic land use, which in combination with future warming will likely result in a rapid desiccation of the lake.

Trees on the tundra: warmer climate might not favor prostrate Larix tree but Betula nana shrub growth in Siberian tundra (Lena River Delta) - Agata Buchwal; Grzegorz Rachlewicz; Birgit Heim; Bennet Juhls (Agricultural and Forest Meteorology, 2023)

Rates of bacterial co-infections and antimicrobial use in COVID-19 patients: a retrospective cohort study in light of antibiotic stewardship - Kathrin Rothe; Susanne Feihl; Jochen Schneider; Fabian Wallnöfer; Milena Wurst; Marina Lukas; Matthias Treiber; Tobias Lahmer; Markus Heim; Michael Dommasch; Birgit Waschulzik; Alexander Zink; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. Bacterial co-infections are associated with unfavourable outcomes in respiratory viral infections; however, microbiological and antibiotic data related to COVID-19 are sparse. Adequate use of antibiotics in line with antibiotic stewardship (ABS) principles is warranted during the pandemic. We performed a retrospective study of clinical and microbiological characteristics of 140 COVID-19 patients admitted between February and April 2020 to a German University hospital, with a focus on bacterial co-infections and antimicrobial therapy. The final date of follow-up was 6 May 2020. Clinical data of 140 COVID-19 patients were recorded: The median age was 63.5 (range 17–99) years; 64% were males. According to the implemented local ABS guidelines, the most commonly used antibiotic regimen was ampicillin/sulbactam (41.5%) with a median duration of 6 (range 1–13) days. Urinary antigen tests for Legionella pneumophila and Streptococcus peumoniae were negative in all cases. In critically ill patients admitted to intensive care units ( n = 50), co-infections with Enterobacterales (34.0%) and Aspergillus fumigatus (18.0%) were detected. Blood cultures collected at admission showed a diagnostic yield of 4.2%. Bacterial and fungal co-infections are rare in COVID-19 patients and are mainly prevalent in critically ill patients. Further studies are needed to assess the impact of antimicrobial therapy on therapeutic outcome in COVID-19 patients to prevent antimicrobial overuse. ABS guidelines could help in optimising the management of COVID-19. Investigation of microbial patterns of infectious complications in critically ill COVID-19 patients is also required.

Assessing the Influence of Water Constituents on the Radiative Heating of Laptev Sea Shelf Waters - Mariana A. Soppa; Vasileios Pefanis; Sebastian Hellmann; Svetlana N. Losa; Jens Hölemann; Fedor Martynov; Birgit Heim; Markus A. Janout; Tilman Dinter; Vladimir Rozanov; Astrid Bracher (Frontiers in Marine Science, 2019)

From Fresh to Marine Waters: Characterization and Fate of Dissolved Organic Matter in the Lena River Delta Region, Siberia - Rafael Gonçalves-Araujo; Colin A. Stedmon; Birgit Heim; Ivan Dubinenkov; Alexandra Kraberg; Denis Moiseev; Astrid Bracher (Frontiers in Marine Science, 2015)

A novel approach for the characterization of tundra wetland regions with C-band SAR satellite data - Barbara Widhalm; Annett Bartsch; Birgit Heim (International Journal of Remote Sensing, 2015)

Assembly and concept of a web-based GIS within the paleolimnological project CONTINENT (Lake Baikal, Russia) - Birgit Heim; Jens Klump; Hedi Oberhänsli; Nathalie Fagel (Journal of Paleolimnology, 2008)

Expression patterns and subcellular localization of a 52 kDa sucrose-binding protein homologue of Vicia faba (VfSBPL) suggest different functions during development - Ute Heim; Qing Wang; Thorsten Kurz; Ljudmilla Borisjuk; Sabine Golombek; Birgit Neubohn; Klaus Adler; Manfred Gahrtz; Norbert Sauer; Hans Weber; Ulrich Wobus (Plant Molecular Biology, 2001)